Correlation between ellipsoid zone thickness and the presence of subretinal drusenoid deposits in age-related macular degeneration - Richard B Rosen; Roland Theodore Smith; Gerardo Ledesma-Gil; Oscar Otero-Marquez; Yuehong Tong; Katy Tai; Gareth M C Lema; Raymond Matthew Bellis; Yang Fei; Brandon Le (BMJ Open Ophthalmology)
Purpose Subretinal drusenoid deposits (SDDs) in age-related macular degeneration (AMD) are associated with systemic vascular diseases that compromise ocular perfusion. We demonstrate that SDDs are associated with decreased ellipsoid zone (EZ) thickness, further evidence of hypoxic damage.Methods Post hoc analysis of a cross-sectional study. 165 AMD subjects (aged 51–100; 61% women). Spectral-domain optical coherence tomography was obtained in both eyes. Masked readers assigned subjects to three groups: drusen only, SDD+drusen (SDD+D) and SDD only. EZ thickness was measured subfoveally and 2000 µm nasally, temporally, superiorly and inferiorly from the fovea. Univariate testing was performed using two-tailed t-tests with Bonferroni correction.Results The mean EZ thickness differences between the SDD+D and drusen-only groups were (in μm) 1.10, 0.67, 1.21, 1.10 and 0.50 at the foveal, nasal, temporal, superior and inferior locations, respectively (p=0.08 inferiorly, otherwise p≤0.01); between the SDD-only and drusen-only groups, the differences were 3.48, 2.48, 2.42, 2.08 and 1.42 (p≤0.0002). Differences in EZ thicknesses across all subjects and between groups were not significantly different based on gender, race or age.Conclusion Subjects with SDDs (±drusen) had thinner EZs than those with drusen only, and the inferior EZ was least affected. EZs were thinnest in SDD-only subjects. This thinning gradation is consistent with progressive destruction of highly oxygen-sensitive mitochondria in the EZ from hypoxia. These findings support the reduced ophthalmic perfusion hypothesis for the formation of SDDs secondary to high-risk systemic vasculopathy.